Analysis of the Influence of Product Design and Perceived Quality on Customer Loyalty Among Hybrid Car Users: The Mediating Role of Customer Satisfaction and Moderating Role of Perceived Value - Muchammad Nur Mafazi Aroli; Rizal Edy Halim (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rise of global decarbonization has significantly transformed the automotive industry, with increasing demand for environmentally friendly vehicles. This study aims to analyze the influence of product design and perceived quality on customer loyalty among hybrid car users in DKI Jakarta, with customer satisfaction as a mediating variable and perceived value as a moderating variable. Integrating Expectancy-Value Theory as its theoretical foundation, this study employs a quantitative approach through an explanatory research design. Data were collected from 200 hybrid car users in DKI Jakarta and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that product design and perceived quality positively influence customer loyalty both directly and indirectly through customer satisfaction. Furthermore, perceived value strengthens the relationship between product design, perceived quality, customer satisfaction, and customer loyalty. This research provides theoretical and practical insights for automotive manufacturers to develop effective differentiation and customer retention strategies in an increasingly competitive market by emphasizing attractive product design, high-quality perceptions, and value propositions that enhance customer satisfaction and loyalty.